Full-scale test and its numerical simulation of a transmission tower under extreme wind loads. Issue 190 (July 2019) - Fu, Xing; Wang, Jia; Li, Hong-Nan; Li, Jia-Xiang; Yang, Li-Dong
Abstract: Accurate simulation of overhead transmission towers under extreme wind loads is complicated due to the eccentrically connected angle section members. First, a full-scale 230 kV suspension tower is manufactured, to which eight loading patterns are applied. The tower successfully passes a 100% loading step test under each pattern and is overloaded to collapse under the final pattern. Then, the framework of a uniform imperfection mode method for the transmission tower is developed to simulate the tower's ultimate performance. The calculated critical loading level and member strains agree well with the experimental results, indicating that it is feasible and reliable to simulate the tower response using the developed method. Finally, an uncertainty analysis is introduced to consider the variations in structural parameters. The tower leg, the initial failure position of the full-scale test, has a failure probability of 8.74%, and its probability of entering the plastic state reaches 92.00%. The failure positions predicted by uncertainty analysis reflect those observed experimentally, providing a feasible approach for finding all the potential failure modes. Highlights: The uniform imperfection mode method for the transmission tower is developed to estimate the strength capacity. A full-scale model is fabricated based on a real operational transmission tower, and a loading test is then carried out. It is feasible and reliable to simulate the tower response using the developed uniform imperfection mode method. The uncertainty analysis provides a feasible approach for finding all the potential failure modes.